Recent Advances in the Synthesis and Applications of Partially Protected N-Glycosylamines - Pradhan, Sheersha; Janhavi, Banoth; Das, Thangamuthu Mohan (Current Organic Chemistry, 2025)
Due to the compatibility of binding and undergoing chemical modification of sugar derivatives with a variety of scaffolds, the design of innovative tools for bio-sensing and bio-marking, energy harvesting, drug design, and delivery is growing steadily. Furthermore, the chemistry of partially protected sugars has not been explored well in terms of its applications in smart materials. However, these sugar derivatives possess a unique characteristic balance between hydrophilic and hydrophobic nature, which makes them act as gelator molecules. Several synthetic strategies pertaining to synthesis and applications are known in the literature. The present review mainly focuses on the partially protected monosaccharide-based N-glycosylamines and their applications, with few examples from O- and C-glycosides.
Keywords: C-glycosides